Analisis Pemeriksaan Bilirubin Total Berdasarkan Variasi Waktu Paparan Cahaya Lampu pada Spesimen - Dwi Wulan Sari; Suryanata Kesuma; Nursalinda Kusumawati (Jurnal Sains & Kesehatan, 2023)
Pre-exam stage one of the most important stages in a laboratory examination which includes patient preparation, specimen reception, specimen processing, identification of specimens and preparation of reagents to be used. Specimens that are not immediately examined can cause the results of the total bilirubin examination to become unstable due to exposure to light which affects the properties of the bilirubin so that the concentration of bilirubin levels in the serum decreases. The purpose of this study was to determine the results of total bilirubin examination based on variations in exposure time to light on the specimens. This research isstudy true experimentby designrandomized pretest-posttest control groupwith 3 treatments, namely exposure to laboratory light on serum specimens for total bilirubin examination (2, 4, and 24 hours). This research was conducted in the hematology and clinical chemistry laboratories, medical laboratory technology department at the East Kalimantan Ministry of Health Polytechnic with a total sample of 40 people. The population in this study were students majoring in medical laboratory technology at the East Kalimantan Ministry of Health Polytechnic. The measurement method used in this research is methodEndPointData analysis used isOne Way ANOVA. The results obtained were clinically and statistically different in the ANOVA test which showed that exposure to light at various times of 2, 4, and 24 hours had a significant effect.